THE ANALYSIS OF CONTEXTS OF STRESS EXPERIENCED BY SOCIAL WELFARE PROFESSIONALS: EXPERIENCE OF LITHUANIA, LATVIA AND GREAT BRITAIN - Alifanoviene, Daiva; Sapelyte, Odeta; Rudytė, Kristina; Orska, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article deals with stress experienced by social welfare professionals in different sociocultural context. The comparison of inter-professional stressogenity shows that the greatest stress is experienced by the representatives of social sphere professions (as social workers, pedagogues). The main aim of the article is to disclose the contexts of stress experienced by social welfare professionals in Baltic countries (Lithuania and Latvia) and Great Britain. Profesionals' experiences were analysed employing the qualitative approach (semi-structured written interview was used). Reconstructing the context of the stress experienced by specialists of social welfare professions of these countries, certain differences showed up.